Controllable rational solutions in nonlinear optics fibers - Abbagari, Souleymanou; Mukam, Serge P.; Houwe, Alphonse; Kuetche, Victor K.; İnç, Mustafa; Doka, Serge Y.; Bouetou, Thomas B. (Springer Heidelberg, 2020)
Based on Darboux matrix method, a generalized Darboux transformation of a generalized nonlinear Schrodinger equation possessing higher-order terms which refer to a femto second pulse propagation in a nonlinear fiber optic is constructed. This nonlinear Schrodinger equation can model the propagation of soliton in a Heisenberg spin chain. Using the above-generalized Darboux transformation, we calculate the first, two and third-order rogue wave solutions and give general formulae for generating Nth-order ones. We discuss the effect of higher-order terms contained in the above equation.
Keywords: Rogue Waves; Equations